Contemporary recent extension and compression in the central Andes. (February 2018) - Tibaldi, A.; Bonali, F.L.
Abstract: Although extension in the high Andes vs. compression in the lowlands has already been widely discussed in the literature, for the first time we recognized both extensional and contractional structures that developed contemporaneously during late Pliocene-Quaternary times in a wide area of the central Andean chain (about 90, 000 km 2 ), where crustal earthquake data are missing. This area comprises north-eastern Chile, south-western Bolivia and north-western Argentina, and extends from the Puna Plateau to the Altiplano-volcanic belt. Late Pliocene-Quaternary folds, with hinge lines trending NNE-SSW to N-S, are mostly located along the westernmost part of the volcanic belt and the eastern part of the Western Cordillera. Locally, there are coeval reverse faults, parallel to the folds, which reach up to the surface; particularly, the Miscanti Ridge, Tolocha Fault and La Casualidad Ridge may be the morphostructural expression of tens-km-long fault-propagation folds, which locally show topographic scarps hundreds of meters high. North and east of the contractional structures, we found evidence of late Pliocene-Quaternary normal faults striking N-S in the southern part of the study area, and NW-SE in the northern part. Well-developed grabens are present in the higher areas of the volcanic belt and in the transition zone with the Puna Plateau. The surface rupture zones of normal fault swarms range 8–24 km in length, with single fault strands up to 18 km long, which are typical of tectonic structures. The distribution in space and time of the studied contractional and extensional structures indicates that they originated in the same time period; we thus address the challenging question regarding the possible origin of the stress sources, by analysing possible causes such as volcanotectonics, high topography, orogeny collapse, and gravitational spreading of the orogen, in relation also with the role played by inherited structures. We finally analyse the relations between the different structures and magma upwelling, and the potential for seismic hazard. Highlights: A structural field survey of the central Andean chain (90, 000 km 2 ) has been done. Both extensional and contractional Plio-Quaternary structures have been mapped. Contractional structures developed under the effect of regional plate tectonic forces. Extensional features result from orogen collapse and inherited structures. Magma paths also followed reverse faults and were guided by folding process.